1996
DOI: 10.1152/jn.1996.75.2.920
|View full text |Cite
|
Sign up to set email alerts
|

Importance of NMDA receptors for multimodal integration in the deep layers of the cat superior colliculus

Abstract: 1. Many sensory events contain multimodal information, yet most sensory nuclei are devoted to the analysis of single-modality information. In the deep superior colliculus (DSC), visual, auditory, and somatosensory information converges on individual multimodal neurons. The responses of multimodal neurons are determined by the temporal and spatial correspondence properties of the converging inputs such that stimuli arising from the same event elicit a facilitated multimodal response. 2. N-methyl-D-aspartate (NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 0 publications
5
41
0
3
Order By: Relevance
“…A large body of work has shown that the NMDA receptor plays a role in the maintenance of working memory (Krystal et al, 1994;Lisman et al, 1998) and multisensory integration (Binns and Salt, 1996) as well as in long-term synaptic plasticity that may substantiate long-term memory (Collingridge et al, 1983;Kerchner and Nicoll, 2008). This study provides evidence that NMDA re- Figure 4.…”
Section: Discussionmentioning
confidence: 59%
“…A large body of work has shown that the NMDA receptor plays a role in the maintenance of working memory (Krystal et al, 1994;Lisman et al, 1998) and multisensory integration (Binns and Salt, 1996) as well as in long-term synaptic plasticity that may substantiate long-term memory (Collingridge et al, 1983;Kerchner and Nicoll, 2008). This study provides evidence that NMDA re- Figure 4.…”
Section: Discussionmentioning
confidence: 59%
“…It was proposed that N-methyl-D-aspartate receptors presented in multisensory neurons in cats provide a molecular mechanism for multiplication (Binns 1999;Binns and Salt 1996). But, Patton and Anastasio (2003) argued that the experimental results of Binns and Salt (1996) as well as previous results by Meredith and Stein (1986) can be reproduced in a model using simple neural mechanisms such as synaptic summation and threshold, not requiring a specialized synaptic multiplication mechanism. A simple threshold mechanism may explain the results of the present study as well: in the bimodal stimuli, the late visual inputs arrive on top of a raised membrane potential and are therefore likely to reach threshold earlier.…”
Section: Mechanisms Of Integrationmentioning
confidence: 99%
“…In the anesthetized cat, unimodal stimuli presented within a bimodal cell's receptive field evoke weak and inconsistent responses, but spatially and temporally coincident bimodal stimuli evoke largely enhanced and consistent responses (1,000% larger than the larger single modality response; Meredith and Stein, 1986). Because stimuli with coincident temporal and spatial characteristics are likely to arise from the same event, response enhancement is thought to be a mechanism for increasing the likelihood of a behavioral response (Stein et al, 1989;Binns and Salt, 1996).…”
Section: Functional Implicationsmentioning
confidence: 99%